Karakteristik Endapan Nikel Laterit pada Zona Limonit dan Zona Saprolit Kecamatan Wolo, Kabupaten Kolaka, Sulawesi Tenggara - Wa Ode Fitria Ramadani; Yayu Indriati Arifin; Ahmad Zainuri (Universitas Negeri Gorontalo, 2026)
This study aims to determine the lithological characteristics, texture, and elemental composition of lateritic nickel deposits in Block X, Wolo District, Kolaka Regency, Southeast Sulawesi Province. The analysis focuses on Ni, Fe, MgO, and SiO₂ contents based on geochemical exploration data obtained from PT Ceria Nugraha Indotama. Data processing was carried out through composite data analysis, descriptive statistical analysis, and visualization using histograms, scatter plots, and ternary diagrams. The results show that the lateritic nickel deposit in the study area can be divided into three main zones: limonite layer, saprolite layer, and bedrock. The limonite layer is characterized by high Fe content (28.65–40.33%) and a clayey texture, while the saprolite layer exhibits higher concentrations of Ni (0.08–2.10%) and MgO (10.29–32.20%) with fine to coarse sandy texture. Intensive laterization processes under humid tropical conditions play a crucial role in the formation, differentiation, and enrichment of lateritic nickel deposits in this lokasi.